1961
DOI: 10.4141/cjps61-022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Date and Frequency of Defoliation on Yield and Quality of Alfalfa

Abstract: In two experiments established in 1950 and 1953, Rhizoma and Grimm alfalfa, each in a simple mixture with timothy, were subjected to seven cutting schedules in the first 2 harvest years. In the third year all plots were cut on tune 15 to determine the effect of the differential defoliation in the preceding years. The two varieties were not significantly different in five of the six seasons but after a winter of severe icing in 1953 Rhizoma outyielded Grimm. The yields of the alfalfa component in the third year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…All other cultivars were intermediate, with no differences among them. Folkins et al (1961) reported that the yield of creeping-rooted Rhizoma was not significantly different from that of tap-rooted 'Grimm' over 5 years. Irvine and McElgunn (1982) reported that yields of tap-rooted 'Beaver' alfalfa were not significantly different from yields of creeping-rooted Roamer.…”
Section: Cultivar 1978 Grazing Grazing Grazing Actual Adjusted' -----mentioning
confidence: 96%
“…All other cultivars were intermediate, with no differences among them. Folkins et al (1961) reported that the yield of creeping-rooted Rhizoma was not significantly different from that of tap-rooted 'Grimm' over 5 years. Irvine and McElgunn (1982) reported that yields of tap-rooted 'Beaver' alfalfa were not significantly different from yields of creeping-rooted Roamer.…”
Section: Cultivar 1978 Grazing Grazing Grazing Actual Adjusted' -----mentioning
confidence: 96%
“…Removal of the first cut at bud ments, average CP in cuts 2 and 3 was 14]9-stage with two, subsequent harvests at the early 77 .3 and li 3-19.4, respectively. IVD was bloom stage also allowed a total of three har- 54.5-60.7 in crft 2 and s6.0-aq.4 in cut 3. vests before early September Twamley (1960) recommended two to three cuts of alfalfa during the summer before the fall rest period. Folkins et al (1961), Langille et al (L965), and Gasser and Lachance (1969) In vitro digestibility of DM of alfalfa was determined from separate freczedried samples, using the method of rilley and rerry (1963) For personal use only. Langille et al (1965) and Gasser and Lachance (1969).…”
mentioning
confidence: 99%